Post-harvest quality model of pineapple guava fruit according to storage and weather conditions of cultivation - Alfonso Parra-Coronado; Gerhard Fischer; Jesús H. Camacho-Tamayo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The post-harvest quality of pineapple guava fruit is determined by the storage and prevailing weather conditions during growth and development. This study proposes a model for post-harvest fruit quality according to the storage and weather conditions in the pineapple guava growing region. Physiologically ripe fruit were collected during two harvests from two locations within the Department of Cundinamarca (Colombia): Tenjo and San Francisco de Sales. The fruits were stored at 18 ± 1 °C (76 ± 5% relative humidity (RH), over 11 days) and at 5 ± 1 °C (87 ± 5% RH, over 31 days), and the quality attributes were evaluated every two days. Models of the most significant physio-chemical quality characteristics of the post-harvest fruit were developed by using the Excel® Solver tool for all data obtained in the two crop periods. The results showed that storage and prevailing weather conditions, which differed according to the altitude of the growing site, had considerable impacts on the physio-chemical characteristics of the fruit throughout the post-harvest ripening process.